2008
DOI: 10.1245/s10434-007-9789-6
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Melanoma Treatment Guidelines in a Community Teaching Hospital: Time Trends and Other Variables

Abstract: Our data suggest that our compliance with NCCN melanoma treatment guidelines was suboptimal. Treatment directed by a surgical oncologist showed the highest rate of adherence to national standards. Further investigation is needed to determine the effect of this on patient outcomes and how best to provide high-quality care to the greatest number of melanoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The evidence on which this is based predominantly focuses on disease affecting the trunk and limbs [12,19,20], and their value in head and neck disease remains unknown [11]. Evidence in this area is particularly useful given the limited scope to achieve the recommended margins in the head and neck region [2,15,17,18]. Five-year survival rates in whole cohort (%)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence on which this is based predominantly focuses on disease affecting the trunk and limbs [12,19,20], and their value in head and neck disease remains unknown [11]. Evidence in this area is particularly useful given the limited scope to achieve the recommended margins in the head and neck region [2,15,17,18]. Five-year survival rates in whole cohort (%)…”
Section: Discussionmentioning
confidence: 99%
“…In the head and neck region, however, excision of this amount of tissue is often not feasible, as it will substantially impair the form and function of the important adjacent structures [2,11,15,16]. Previous reports are of achievement of the desired margins in the range of 50-70% in this area [15,17,18]. The current consensus is that 'narrower margins should be considered as very reasonable in all those areas where a 2-cm margin would meet with anatomical, functional or cosmetic constraints', though there is very little published data to support such recommendations [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in cancer management related to these factors has been studied in many malignancies including breast cancer, prostate cancer, colon cancer and pancreatic cancer [Blackman and Masi, 2006;Olopade et al 2006;Polite et al 2006;Chen et al 2008;Halpern et al 2008]. Prior studies in melanoma demonstrated that hospital type was one of the factors influencing compliance with National Comprehensive Cancer Network (NCCN) treatment guidelines [Erickson et al 2008;Bilimoria et al 2009]. These studies raise a possibility that the quality of care and possibly outcomes may differ by hospital type.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier this year, Erickson et al 2 reviewed the charts of 252 clinically node-negative melanoma patients treated at a community teaching hospital and found a significant rate of noncompliance with NCCN guidelines. Excision margins conformed to the guideline standards in 87% of in situ and thin (T1) tumors but only 60% of thicker tumors (T2-4).…”
mentioning
confidence: 99%